Cost-effectiveness analysis of uterus transplantation vs. gestational carrier for treatment of absolute uterine factor infertility in the United States - Walter, Jessica R.; Richards, Elliott G.; Johannesson, Liza; Falcone, Tommaso; Jungheim, Emily; Testa, Giuliano; O’Neill, Kathleen E.; Harvie, Heidi S. (Fertility and sterility, 2025)
To compare the cost-effectiveness of treatment for patients with absolute uterine factor infertility to achieve one or two singleton births by gestational carrier vs. uterus transplant. Decision analysis from the US healthcare sector perspective, with time horizons to achieve one or two singleton births. Patients with uterine factor infertility desiring family building. Gestational carrier or uterus transplant. Incremental cost-effectiveness ratios, comparing the costs (2020 US Dollars) and effectiveness (quality-adjusted life years [QALYs] and live births) to achieve one or two births by gestational carrier vs. uterus transplant. In the base case of one singleton birth, the overall cost using a gestational carrier was $97,712.90 ($56,985.20–$153,084.20) compared with $116,137.20 ($67,142.88–$182,290.86) after uterus transplant. Quality-adjusted life years were higher in the gestational carrier arm (0.93) compared with the uterus transplant (0.90) and overall rates of live birth were also higher in the gestational carrier arm (94%) compared with the uterus transplant arm (77%). Costs of the gestational carrier and uterus transplant recipient were the most significant cost variables in the model. Monte Carlo simulation showed that uterus transplant had a 37% chance of being the cost-effective strategy for a single live birth at a willingness to pay of $150,000/QALY. In the case of two singleton births, the cost using a gestational carrier was $186,278.56 ($103,597.81–$296,010.27) compared with $164,276.84 ($111,961.91–$229,394.43) after uterus transplant. Quality-adjusted life years were again higher in the gestational carrier arm (0.93) than the uterus transplant (0.89). Overall rates of two live births were also higher in the gestational carrier arm (86%) compared with the uterus transplant arm (66%). Monte Carlo simulation showed that uterine transplant has a 62% chance of being the cost-effective strategy for two live births at a willingness to pay $150,000/QALY. In the United States, treatment of uterine factor infertility with a gestational carrier is likely the most cost-effective approach for patients delivering a single child. However, the absolute costs associated with uterus transplants were 14% less than a gestational carrier for those having two live singleton births. Análisis de costo efectividad de transplante uterino vs subrogación para el tratamiento de la infertilidad por factor uterino absoluto en Estados Unidos Comparar costo efectividad del tratamiento para pacientes con infertilidad por factor uterino absoluto para lograr uno o dos nacimientos únicos a través de gestación subrogada vs transplante uterino. Análisis de decisiones desde la perspectiva del sector sanitario estadounidense, con horizontes temporales para lograr uno o dos nacimientos únicos. Pacientes con infertilidad por factor uterino deseando formar una familia. Subrogación o transplante uterino. Razones de costo efectividad incremental, comparando los costos (2020 dólares estadounidenses) y efectividad (año de vida ajustado por calidad [QALYs] y nacidos vivos) para lograr uno o dos nacimientos por gestación subrogada vs transplante uterino. En el caso base de un nacimiento único, el costo total en gestación subrogada fue $97,712.90 ($56,985.20-$153,084.20) comparado con $116,137.20 ($67,142.8-$182,290.86) para transplante uterino. Los años de vida ajustados por calidad fueron mayores en la rama de gestación subrogada (0.93) comparado con el transplante uterino (0.90) y las tasas generales de nacido vivo fueron también mayores en la rama de gestación subrogada (94%) comparadas con la rama de transplante uterino (77%). Los costos de la portadora gestacional y la receptora del transplante uterino fueron las variables de costos más significativas en el modelo. La simulación Monte Carlo mostró que el transplante uterino tuvo un 37% de chance de ser la estrategia costo efectiva para un solo nacido vivo con voluntad de pagar $150,000/QALY. En el caso de dos nacimientos únicos, el costo de gestación subrogada fue $186,278.56 ($103,597.81-296,010.27) comparado con $164,276.84 ($111,961.91-$229,394.43) para transplante uterino. Los años de vida ajustados por calidad fueron otra vez mayores en la rama de gestación subrogada (0.93) que en la de transplante uterino (89%). Las tasas generales de dos nacidos vivos también fueron mayores en la rama de gestación subrogada (86%) comparada con la rama de transplante uterino (66%). La simulación Monte Carlo mostró que el transplante uterino tiene un 62% de chance de ser una estrategia costo efectiva para dos nacidos vivos con voluntad de pagar $150,000/QALY. En los Estados Unidos, el tratamiento de la infertilidad por factor uterino con gestación subrogada es probablemente el enfoque más rentable para pacientes que tienen un solo niño. Sin embargo, los costos absolutos asociados con transplante uterino fueron 14% menores que en gestación subrogada para aquellos con dos nacimientos únicos vivos.